Democratic Republic Of Timor-Leste : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
Timor-Leste had made good progress in establishing the basis for a stable and healthy economy prior to the civil unrest in 2006, although it remains one of the poorest countries in the world. This 2006 Article IV Consultation highlights that real non-oil GDP growth turned positive in 2004-05 after contracting for two years. Macroeconomic stability was achieved through the early adoption and maintenance of prudent fiscal and monetary policies. The authorities have maintained a policy of avoiding domestic or external borrowing, hence there is no public sector debt.